Faktor-faktor Penghambat Ritel Berjaringan Masuk ke Kota Padang sampai Tahun 2017 - Balqis, Monica (Jurnal Politik, 2018)
This article explains how local government can hamper the development of retail net¬work in Padang City. In the case of Padang, the local government in the era of economic decentralization is assumed to encourage openness to investment, instead of using the instrument of authority to block the entry of retail network. The author uses a qualitative-descriptive method to answer the problem by digging primary data and supplemented by published data. By analyzing through a barrier to entry mechanism, this mechanism stipulates that local governments inhibit the entry of retail network in order to prevent competition with local retailers through several key factors. This study approves that there are three main factors that hamper the entry of retail network in Padang City: government intervention in the retail industry, government policy is applied as market entry criteria and bureaucratic barrier that cause licensing delays.